HIF1α Regulates IL17 Signaling Pathway Influencing Sensitivity of Taxane-Based Chemotherapy for Breast Cancer - Dai, Huijuan; Sheng, Xiaonan; Wang, Yaohui; Zhou, Liheng; Lin, Yanping; Du, Yueyao; Yang, Fan; Sha, Rui; Peng, Jing; Yao, Linli; Yin, Wenjin; Lu, Jinsong (Frontiers in Cell and Developmental Biology, 2021)
Hypoxia induced chemotherapy resistance is the main hinder for solid tumor treatment. hypoxia inducible factor–1a (HIF1a), an adaptive gene of hypoxia condition, played an important role in chemotherapy sensitivity in various cancer types and various therapeutic regimens. This study focused on the impact of HIF1a on predicting response and survival of taxane-based neoadjuvant therapy (NAT) for breast cancer (BC) patients and investigated the concrete mechanism of HIF1a mediating paclitaxel chemo-insensitivity. We evaluated HIF1a expression immunohistochemically from 108 BC patients’ biopsies receiving paclitaxel-cisplatin NAT. Univariate and multivariate logistic regression analysis revealed high HIF1a expression led to lower rate of pathological complete response (pCR) and worse prognosis. Analysis of GEO datasets also indicated negative association between HIF1a and response of taxane-based NAT in BC. KEGG (Kyoto Encyclopedia of Genes and Genomes) pathway enrichment of differential expression genes (DEGs) in different HIF1a expression group from TCGA database showed that HIF1a participated in IL-17 signaling pathway. Correlation analysis suggested that HIF1a was positively related to IL-17 pathway. CXCL10 was the only DEG in IL-17 pathway inversely relating to NAT response. Experiments in vitro verified that HIF1a/IL-17 pathway influences paclitaxel sensitivity to BC cells. Correlation analysis between HIF1a/IL-17A/ CXCL10 and infiltration of immune cells in BC uncovered that high expression of all above three genes were positively correlated to neutrophils infiltration in BC. Collectively, our findings shed novel insight into the mechanism of chemotherapy resistance and implied HIF1a inhibitor may be a promising drug combining with traditional chemotherapeutic drug to increase the chemotherapy efficacy.